The Shape of Lightning. The Nietzsche's poetic in Thus Spoke Zarathustra (2006)
The affirmation of Nietzsche in Ecce Homo, from Thus Spoke Zaratustra, guides an interpretation of the purpose. In the case, not only reading about philosophy but -mainly- writing, experimentation of knowledge, world experience. Not only in what has to do